2020
DOI: 10.1002/aenm.202002095
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Stability between Donor and Acceptor Materials in a Fullerene‐Free Bulk Heterojunction Solar Cell Blend

Abstract: With rapid advances in material synthesis and device performance, the long‐term stability of organic solar cells has become the main remaining challenge toward commercialization. An investigation of photodegradation in blend films of the donor polymer poly(3‐hexylthiophene) (P3HT) and the rhodanine‐flanked small molecule acceptor 5,5′‐[(9,9‐dioctyl‐9H‐fluorene‐2,7‐diyl)bis(2,1,3‐benzothiadiazole‐7,4‐diylmethylidyne)]bis[3‐ethyl‐2‐thioxo‐4‐thiazolidinone] (FBR) is presented in an ambient atmosphere. The photobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…40 Instabilities can also arise in the presence of photogenerated singlet oxygen, which can cause photobleaching of OSC materials. 48 Consideration should therefore be given to both the material design to lower the LUMO below À4.0 eV and improve delocalisation of the LUMO across the entire polymer backbone (through improved planarity and an acceptor-acceptor configuration), in addition to the device architecture and processing conditions to maximise charge transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Instabilities can also arise in the presence of photogenerated singlet oxygen, which can cause photobleaching of OSC materials. 48 Consideration should therefore be given to both the material design to lower the LUMO below À4.0 eV and improve delocalisation of the LUMO across the entire polymer backbone (through improved planarity and an acceptor-acceptor configuration), in addition to the device architecture and processing conditions to maximise charge transport.…”
Section: Discussionmentioning
confidence: 99%
“…47 More specifically, water is reduced at potentials lower than À0.658 V (À3.7 eV), and oxygen can undergo reduction to hydrogen peroxide by electron transfer from the excited OSC negative polaron to a dioxygen molecule at +0.024 V (À4.4 eV). 47,48 Oxygen can also undergo a four electron reduction at +0.571 V (À4.9 eV), so without taking overpotentials into account, for an n-type polymer to be stable to water, the doped (reduced) polymer should be oxidised at a potential higher than À0.658 V, furthermore for it to be stable to both oxygen and water, it needs to be oxidised higher than +0.571 V (Fig. 2).…”
Section: Stability Of N-type Organic Semiconducting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35b ] Recently, the study of photooxidation of P3HT:FBR system ( Figure ) demonstrated that fast donor–acceptor charge transfer leaves a negligible amount of triplet excited states for the generation of 1 O 2 , but the mobile electrons of FBR can energetically transfer to O 2 , inducing a higher production rate of O 2 •− than that in the neat P3HT film. [ 32 ] Note that the acceptor with a shallow LUMO (lowest unoccupied molecular orbital) level would further facilitate the formation of O 2 •− . [ 36 ] Furthermore, it was also shown that the degradation of P3HT will reduce the exciton dissociation efficiency, thereby increasing the triplet excitons in FBR, which would generate more 1 O 2 to photobleach both materials.…”
Section: Intrinsic Instability For Freasmentioning
confidence: 99%
“…c) Jablonski diagrams for the P3HT:FBR blend with the 1 O 2 generation mechanism. Reproduced with permission [32]. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%